Communication Network Analysis Model in the Nehemia Javanese Christian Church, Jakarta - Yudhistira, Naftali; Rinanto Sigit, Ridzki; Sunarto (PT. BERBAGI TEKNOLOGI SEMESTA, 2024)
This research aims to determine and analyze the structural and external factors that influence communication/interaction at GKJ Nehemia which influences communication/interaction to shape organizational communication so that their services can be well received by the wider community. The result of this research is two-way communication between pastors, councils, and commissions. In activities/tasks carried out together, two-way communication is flowing, and there are not significant obstacles. Communication media that represents current communication channels. Media such as WhatsApp, email, Congregation News, and telephones are used together and responsibly. The assembly or commission is proactive in providing information about weekly worship services at any time. Activities/worship/events that will be presented in the future will be conveyed if there are congregations that still do not understand or have not received complete information. They do not hesitate to notify activities/worship/events well in advance so that the congregation can prepare everything before hand. Church employees/staff who are alert in providing information as expressed by the pastor, chairman of the council, and secretary of the council. They prepare information materials to be communicated to the entire congregation based on existing directions. They are also diligent in asking questions and providing input if necessary.